2018
DOI: 10.1002/jssc.201800006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of new psychoactive substances in human urine by ultra‐high performance supercritical fluid and liquid chromatography: Validation and comparison

Abstract: New psychoactive substances represent serious social and health problem as tens of new compounds are detected in Europe annually. They often show structural proximity or even isomerism, which complicates their analysis. Two methods based on ultra high performance supercritical fluid chromatography and ultra high performance liquid chromatography with mass spectrometric detection were validated and compared. A simple dilute-filter-and-shoot protocol utilizing propan-2-ol or methanol for supercritical fluid or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In addition, UHPSFC is a green technology (or clean technology), with shorter analysis time, less use of organic solvents, and wider range of applications. 6,7 UHPSFC for the analysis of pentaerythritol fatty acid esters has the merits of short analysis time and high separation efficiency, owing to the properties of the supercritical fluid. To the best of our knowledge, no paper has been published on the separation of pentaerythritol fatty acid esters using UHPSFC.…”
Section: Accordingly Sfc Facilitates High-throughput and High-resolumentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, UHPSFC is a green technology (or clean technology), with shorter analysis time, less use of organic solvents, and wider range of applications. 6,7 UHPSFC for the analysis of pentaerythritol fatty acid esters has the merits of short analysis time and high separation efficiency, owing to the properties of the supercritical fluid. To the best of our knowledge, no paper has been published on the separation of pentaerythritol fatty acid esters using UHPSFC.…”
Section: Accordingly Sfc Facilitates High-throughput and High-resolumentioning
confidence: 99%
“…Accordingly, SFC facilitates high‐throughput and high‐resolution analysis. In addition, UHPSFC is a green technology (or clean technology), with shorter analysis time, less use of organic solvents, and wider range of applications . UHPSFC for the analysis of pentaerythritol fatty acid esters has the merits of short analysis time and high separation efficiency, owing to the properties of the supercritical fluid.…”
Section: Introductionmentioning
confidence: 99%
“…This aspect is being currently investigated by several authors, with a growing number of publications [38,39,45,47,49,75] showing that the validation procedure in SFC-MS yields similar, if not even better results than LC-MS. Indeed, during different validation processes of SFC-MS methods, it was found that SFC-MS manages to provide better results in terms of identification, reproducibility, precision and accuracy when compared to LC-MS [47,75]. These findings are extremely important in establishing SFC-MS itself as a technique that is compatible with regulated bioanalytical laboratories.…”
Section: Today Sfc-ms Can Be Considered As a Complementary Techniquementioning
confidence: 99%
“…A fast chromatographic run (1.6 min) was sufficient to analyze a mixture of 15 NPS and separate isomers . For the detection and quantification of NPS in urine samples, the SFC-MS method was competitive with LC-MS …”
Section: Introductionmentioning
confidence: 99%